Beginner's step-by-step coding course Learn computer programming the easy way (London : Penguin random house, 2020)
Learning to code has never been easier than with this essential guide to computer programming for beginners. With this visual guide to computer programming for beginners, it has never been easier to learn how to code. Coding skills are in high demand and the need for programmers is still growing. Covering three of the most popular languages for new coders, this book uses a graphic method to break complex subjects into user-friendly chunks, bringing essential skills within easy reach. Each chapter contains tutorials on practical projects designed to teach you the main applications of each language, such as building websites, creating games, and designing apps. The book also looks at many of the main coding languages that are out there, outlining the key applications of each language, so you can choose the right language for you. You'll learn to think like a programmer by breaking a problem down into parts, before turning those parts into lines of code. Short, easy-to-follow steps then show you, piece by piece, how to build a complete program. There are challenges for you to tackle to build your confidence before moving on. Written by a team of expert coders and coding teachers, Beginner's Step-by-Step Coding Course is the ideal way to get to set you on the road to code.
Keywords: Computer - Coding